Expansions in Paid Parental Leave and Mothers' Economic Progress - Gozde Corekcioglu; Marco Francesconi; Astrid Kunze (Center for Economic Studies and ifo Institute (CESifo), 2022)
We examine the impact of government-funded universal paid parental leave extensions on the likelihood that mothers reach top-pay jobs and executive positions, using eight Norwegian reforms. Up to a quarter of a century after childbirth, such reforms neither helped nor hurt mothers' chances to be at the top of their companies' pay ranking or in leadership positions. We detect no differential effect across many characteristics, and no impact on other outcomes, such as hours worked and promotions. No reform affected fathers' pay or the gender pay gaps between mothers and their male colleagues and between mothers and their partners.
Keywords: H42; J13; J16; J18; M12; M14; 330; gender inequality; within-firm pay ranking; glass ceiling; leadership; top executives